THE IMPACT OF FRONTIER ZONES OF PUBLIC POLICY ON THE DEVELOPMENT OF SOCIAL CONFLICTS - STADNIICHUK, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Frontier zones of public policy are becoming an increasingly noticeable phenomenon in modern society, especially in the context of growing public activity and access to information. Studying the impact of these zones on the development of social conflicts is important for understanding the dynamics of social relations and finding ways to overcome them. Insufficient attention to this problem in scientific and practical discourse creates the need for further research and analysis in order to effectively influence the development of public policy and ensure stability in society. Frontier zones of public policy in modern society are of great interest both among scientists and practitioners. However, insufficient attention to the study of the influence of these zones on the development of social conflicts leaves the question of their role and significance in society unresolved.Against the background of the growing importance of public participation in management processes, the study of the influence of frontier zones of public policy on the development of social conflicts becomes an urgent task. This becomes especially important in the context of the growing role of civil society, the media and other actors that influence the formation of public opinion and decision-makingThe article examines the impact of frontier zones of public policy on the development of social conflicts in contemporary society. Key aspects of interaction between state structures and society are considered, including processes of formation and implementation of public interests, influence of leaders and ideologues, media and communication technologies. Various frontier zones are analyzed, such as decision-making processes, media sphere, information warfare, and interaction with the public through different communication channels. The research aims to identify mechanisms of conflict emergence and development in these zones and develop ways to overcome and manage them to ensure stability in society. The results of the analysis may be useful for understanding social processes and developing political strategies for conflict management in modern society.Turning to traditional interpretations of public policy, the author justifies the need for analytical correction of its content based on identifying universal parameters of publicity reflecting the unique format of open (vocal) relations between the state and society. In this context, three social spaces of the public sphere are highlighted, each determining the possibilities of citizen participation in governance and strengthening the social orientation of government policy. The peculiarities of implementing such a variant of state public policy are briefly outlined.
Keywords: public administration; frontier zones; social conflicts; business; efficiency; development